Binding between heparin and the integrin VLA-4 - Schlesinger, Martin; Simonis, Dirk; Schmitz, Patrick; Fritzsche, Juliane; Bendas, Gerd (Thrombosis and Haemostasis, 2009)
Heparin possesses antimetastatic effects that were related to various molecular mechanisms beyond anticoagulant activities. The ability of heparin to interfere with the function of adhesion receptors in the metastatic course appears as a promising therapeutic approach. This refers to numerous findings that heparin attenuates metastasis in a selectin-dependent manner. We recently demonstrated that heparin interferes with the integrin VLA-4 on murine melanoma cells binding to VCAM-1. To confirm this activity and to obtain further insight into molecular recognition of heparin by VLA-4, we investigated the inhibition of VLA-4 mediated binding of human melanoma MV3 cells to immobilized VCAM-1 by different heparins. The size of heparin has an important impact on inhibition. Unfractionated heparin (UFH) and tinzaparin, a low-molecular-weight heparin (LMWH) representing a mean of about 18– 20 monomers, displayed high inhibitory activity. Fractionating tinzaparin to 14– 18 monomers reduced inhibition slightly, while the pentasaccharide fondaparinux was without effects. To confirm molecular recognition of tinzaparin by VLA-4,a surface acoustic wave-biosensor was applied. A VLA-4 containing membrane preparation of MV3 cells was immobilised at the sensors to allow for detection of kinetic binding constants of tinzaparin compared to VCAM-1. Tinzaparin binds to VLA-4 with affinity in the low micromolar range (4.61× 10−6 M), which clearly indicates specific molecular recognition. Furthermore, tinzaparin displays a nearly identical koff compared toVCAM-1 (5.13× 10−3 s-1 versus 3.44× 10–3 s-1) which is evident for interference with the ligand binding. The data provide evidence for a direct confirmation of heparin binding to VLA-4 and thus, contribute to understand the antimetastatic activity of heparin.
Keywords: Heparin; melanoma cell adhesion; VLA-4; antimetastatic activity